Indoor Social Networks in a South African Township: Potential Contribution of Location to Tuberculosis Transmission - Wood, Robin (Public Library of Science, 2012)
BACKGROUND: We hypothesized that in South Africa, with a generalized tuberculosis (TB) epidemic, TB infection is predominantly acquired indoors and transmission potential is determined by the number and duration of social contacts made in locations that are conducive to TB transmission. We therefore quantified time spent and contacts met in indoor locations and public transport by residents of a South African township with a very high TB burden. METHODS: A diary-based community social mixing survey was performed in 2010. Randomly selected participants (n = 571) prospectively recorded numbers of contacts and time spent in specified locations over 24-hour periods. To better characterize age-related social networks, participants were stratified into ten 5-year age strata and locations were classified into 11 types. RESULTS: Five location types (own-household, other-households, transport, crèche/school, and work) contributed 97.2% of total indoor time and 80.4% of total indoor contacts. Median time spent indoors was 19.1 hours/day (IQR:14.3–22.7), which was consistent across age strata. Median daily contacts increased from 16 (IQR:9–40) in 0–4 year-olds to 40 (IQR:18–60) in 15–19 year-olds and declined to 18 (IQR:10–41) in ≥45 year-olds. Mean daily own-household contacts was 8.8 (95%CI:8.2–9.4), which decreased with increasing age. Mean crèche/school contacts increased from 6.2/day (95%CI:2.7–9.7) in 0–4 year-olds to 28.1/day (95%CI:8.1–48.1) in 15–19 year-olds. Mean transport contacts increased from 4.9/day (95%CI:1.6–8.2) in 0–4 year-olds to 25.5/day (95%CI:12.1–38.9) in 25–29 year-olds. CONCLUSIONS: A limited number of location types contributed the majority of indoor social contacts in this community. Increasing numbers of social contacts occurred throughout childhood, adolescence, and young adulthood, predominantly in school and public transport. This rapid increase in non-home socialization parallels the increasing TB infection rates during childhood and young adulthood reported in this community. Further studies of the environmental conditions in schools and public transport, as potentially important locations for ongoing TB infection, are indicated.